PERAN BANTUAN PANGAN NON TUNAI (BPNT) DALAM MENDUKUNG PEREKONOMIAN UMAT MUSLIM DI DESA LEBBAE KECAMATAN AJANGALE - Yunus, Ananda Agustin (Jurnal Ekonomi dan Bisnis (EK&BI), 2025)
This study discusses the role of the Non-Cash Food Assistance Program (BPNT) in supporting the economy of the Muslim community in Lebbae Village, Ajangale District. The main issues addressed are the effectiveness of BPNT in reducing the economic burden of beneficiary families (KPM) and the accuracy of the aid distribution targets. The aim of this research is to describe BPNT's contribution to improving the economic welfare of the local community and to identify obstacles in its implementation. Using a field research method with a qualitative approach, data were collected through observation, in-depth interviews with KPM, the Village Head, and the Head of the Social Affairs Division, as well as documentation. The results show that BPNT helps reduce household food expenditures, increases the economic security of families, and stimulates local economic activity through e-warong (electronic stalls). However, challenges remain, such as limited food variety and uneven distribution among beneficiaries. In conclusion, BPNT has a positive impact on the economy of the Muslim community in Lebbae Village, although improvements in implementation are needed to maximize its benefits.